Regional Economic Outlook, April 2008, Europe : Reassessing Risks. (Regional Economic Outlook, 2008)
Europe is facing slower growth as a result of protracted financial turbulence and spillovers from the U.S. Meanwhile, inflation has risen sharply. Policymakers in advanced economies will have to continue to support financial markets and balance risks to real activity with the need to anchor inflation. Emerging Europe is well placed to continue to grow, albeit at a slower pace, amid concerns about overheating and external imbalances in several countries. Sound macroeconomic policies and structural reforms will be necessary to ensure a soft landing in these countries and smooth convergence throughout the region.